Narrative Review of Nepal’s Health Systems in Federal Context: From Margin to Mainstream - Bhandari, Jhabindra (International Journal of Atharva, 2025)
Nepal’s health systems face a number of diverse yet intersecting challenges and opportunities to ensure inclusive and equitable health care services for all. Poverty, difficult geography, limited transport facilities, poor health infrastructure, and unavailability of comprehensive health care in the health facilities are hindering people’s access to quality health care in rural areas. On the other side, investments in other sectors such as education, agriculture, transport, urban development, environment, water and sanitation are limited in rural areas. In this context, the crucial role of provincial and local governments must be enhanced to effectively implement the national policies, strategies, and related guidelines at local level. Moving forward, participatory and inclusive health planning should be a priority agenda of local governments to ensure no one is left behind. From implementation perspective, there lacks clarity in terms of coordination, authority, transparency and social accountability at all levels. Despite notable progress, the institutional bottlenecks are barriers in driving change for improved health outcomes. Surely, this will continue to have creeping impacts on performance of health sector at large. The voices of the vulnerable groups are not sufficiently heard yet by political leaders, civil society and health service providers.